Investigating pay disparities among individuals with protected characteristics in Wales using income linked data - Curds, Matthew; Akbari, Ashley; Robinson, Lucy; Bedston, Stuart; Abbasizanjani, Hoda (International Journal of Population Data Science, 2026)
This study, conducted under the ADR Wales Ymateb (formally the Major Societal Challenges) programme, investigates pay disparities among individuals with protected characteristics across Wales using newly available HMRC annual earnings data linked within the SAIL Databank. This is the first time population-level earnings data has been integrated into SAIL, offering a unique opportunity to assess its research utility and inform equality-focused policy development. Our analysis explores income differences by gender, ethnicity, disability, and other protected characteristics, moving beyond traditional gender pay gap measures to consider overall earnings and intersectional disadvantage. Intersectionality—where multiple forms of inequity compound—we haveexamined to identify groups most at risk of systemic inequality. We have linked income data to demographic, socioeconomic, and labour market variables from sources including the Welsh Demographic Service Dataset and ONS Census data, enabling granular analysis of pay gaps across Wales. The project employs descriptive and inferential statistical techniques, including regression modelling and sensitivity analyses, to understand patterns and drivers of income inequality. Published findings will provide baseline measures for Welsh Government commitments, including the Wellbeing of Future Generations Act and the Anti-Racist Wales Action Plan, which aim to eliminate pay gaps by 2050. By leveraging administrative data linkage at scale, this research will deliver robust evidence to support fair pay policies and advance understanding of structural inequalities in Wales. Outputs will inform national indicators, policy evaluations, and long-term strategies to reduce disparities and promote equity across the Welsh workforce.